2012
DOI: 10.1042/bj20111317
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric antibody inhibition of human hepsin protease

Abstract: Hepsin is a type II transmembrane serine protease that is expressed in several human tissues. Overexpression of hepsin has been found to correlate with tumour progression and metastasis, which is so far best studied for prostate cancer, where more than 90% of such tumours show this characteristic. To enable improved future patient treatment, we have developed a monoclonal humanized antibody that selectively inhibits human hepsin and does not inhibit other related proteases. We found that our antibody, hH35, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 57 publications
2
26
1
Order By: Relevance
“…Interestingly, a specific antibody acting as an allosteric inhibitor of catalytic activity that binds at the periphery of the substrate binding site of HGFA has been reported . This allosteric inhibition mechanism may have implications for the development of innovative strategies to regulate HGF/SF‐activating TTSPs possibly involved in cancer progression …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Interestingly, a specific antibody acting as an allosteric inhibitor of catalytic activity that binds at the periphery of the substrate binding site of HGFA has been reported . This allosteric inhibition mechanism may have implications for the development of innovative strategies to regulate HGF/SF‐activating TTSPs possibly involved in cancer progression …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition to Kunitz domain-1, development of several antibodies specifically inhibiting Hepsin have been reported [13, 29, 30]. While Hepsin antibodies are likely to be useful for prostate cancer imaging, the therapeutic use of these antibodies for tumor eradication may be somewhat limited due to the prominent expression of endogenous Hepsin in hepatocytes [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these inhibitors, studies using antibodies targeting hepsin have also been reported. The monoclonal, humanized, allosteric antibody, hH35, inhibits hepsin enzymatic activity at nanomolar concentrations [127]. Fab25, found by screening a Fab phage display library, is another allosteric inhibitor [78], although effects in either cell-or animal-based systems remain unexplored.…”
Section: Ttsps As Novel Therapeutic Targets In Cancermentioning
confidence: 99%